AN ANALYSIS OF THINKING ORDER OF READING COMPREHENSION QUESTIONS IN ENGLISH TEXTBOOK FOR YOUNG FORESTERS OF FORESTRY VOCATIONAL SCHOOL OF SAMARINDA - Muchlis, Muchlis (JURNAL NALAR PENDIDIKAN, 2015)
This study aimed at investigating thinking order of reading comprehension questions in English textbook for young foresters of Forestry Vocational school of Samarinda. It also used content analysis method in which the researcher collected, analyzed and classified reading questions based on Bloom Taxonomy cognitive level as well as high and low order thinking. The findings showed that the reading comprehension questions covered all Bloom’s Taxonomy cognitive levels. They were knowledge, comprehension, application, analysis, synthesis and evaluation. The most frequently appeared were knowledge and comprehension level. However, most of the questions were dominated low order thinking and had small number in high order thinking. Besides that, it suggested recommendations and pedagogical implications to develop students thinking skills ability in English classroom.Keywords: English textbook, Reading comprehension question, Thinking skill, Bloom’s taxonomy.